2005
DOI: 10.1021/ol0500259
|View full text |Cite
|
Sign up to set email alerts
|

Increased Structural Complexity Leads to Higher Activity:  Peptides as Efficient and Versatile Catalysts for Asymmetric Aldol Reactions

Abstract: [reaction: see text] Peptides containing a secondary amine and a carboxylic acid in a specific orientation to each other are presented as highly efficient catalysts for asymmetric aldol reactions: (1) their activity is considerably higher compared to that of proline, and (2) the enantioselectivity of the peptidic catalysts can be changed from (R)- to (S)-selectivity by simple modifications of the secondary structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(131 citation statements)
references
References 15 publications
3
125
0
3
Order By: Relevance
“…Finally, proline-derived small peptides can frequently serve as efficient chiral organocatalysts. [132][133][134][135][136][137] Although the peptide-series catalysts usually have molecular weights about five times as large as proline itself, they work well even in THF/water mixed solvent system to give excellent enantioselectivities of up to 96% ee (Scheme 39). A surprising result in this system is their reversed regioselectivity with regard to the methyl group: the reaction took place preferentially at the methyl group of hydroxyacetone to give the 1,4-diol products.…”
Section: 115mentioning
confidence: 99%
“…Finally, proline-derived small peptides can frequently serve as efficient chiral organocatalysts. [132][133][134][135][136][137] Although the peptide-series catalysts usually have molecular weights about five times as large as proline itself, they work well even in THF/water mixed solvent system to give excellent enantioselectivities of up to 96% ee (Scheme 39). A surprising result in this system is their reversed regioselectivity with regard to the methyl group: the reaction took place preferentially at the methyl group of hydroxyacetone to give the 1,4-diol products.…”
Section: 115mentioning
confidence: 99%
“…131 Finally, proline-derived small peptides can frequently serve as efficient chiral organocatalysts. [132][133][134][135][136][137] Although the peptide-series catalysts usually have molecular weights about five times as large as proline itself, they work well even in THF/water mixed solvent system to give excellent enantioselectivities of up to 96% ee (Scheme 39). 134 A surprising result in this system is their reversed regioselectivity with regard to the methyl group: the reaction took place preferentially at the methyl group of hydroxyacetone to give the 1,4-diol products.…”
Section: Prolinamide Catalystsmentioning
confidence: 99%
“…15 Solution phase studies revealed that, particularly with 1, 1 mol % is sufficient to obtain aldol products in up to quantitative yields and up to 90% enantiomeric excess. Compared to the rigid, small organocatalyst proline, 1 is more than 30-fold more active with either comparable or higher selectivity.…”
Section: Introductionmentioning
confidence: 99%